Evaluasi Data Satelit GPM (Global Precipitation Measurement) pada DAS Kemuning di Banjarbaru, Kalimantan Selatan - Noordiah Helda; Nilna Amal; Humaira Afrila; Dwi Surya Saputri; Erisa Erisa; Muhammad Risky Maulana; Muhammad Irfan (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
In the hydrological cycle, rainfall is one of the vital components for the environment. Rainfall data plays an important role in determining the amount of runoff that occurs. Accurate and complete rainfall data estimates are needed in managing water resources; which are still limited, especially for watersheds with less field rainfall measurement stations. This study aims to analyze the use of satellite-based rainfall data, especially GPM (Global Precipitation Measurement) as an alternative rainfall data for watersheds with minimal observational rainfall data. In this study, secondary data collection was carried out by downloading observational rainfall data via BMKG Online and GPM satellite-based rainfall data for the period of 2018-2023. Several statistical methods were used to assess satellite performance and the relationship between BMKG and GPM data in Kemuning Watershed. From the results of the analysis, it can be seen that the correlation value between BMKG and GPM shows sufficient correlation (r = 0.45) and as much as 93% of GPM satellite data can be explained by BMKG data factors. Thus, GPM satellite data can be used as an alternative rainfall data, especially for watersheds with limited measurement stations.